In Vitro Effect of Mannitol Stress and γ-ray on Secondary Products From Golden Sunrise Cherry Tomato Callus - Mizil, Shaimaa N.; ElKaaby , Ekhlas. A.J.; Al-Shammary, Maher Z. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Effect of drought stress induced by mannitol on secondary products in callus of Golden Sunrise cherry tomatoes were studied in vitro. Seeds were irradiated with gamma at the doses (0, 20, or 40 Gy), and germinated on Murashige and Skoog, (MS) basal medium. Callus were initiated from cotyledon leaf explants using a combination of (2.0 kin + 2.0 IAA mg. l-1) then transferred into MS medium supplemented with mannitol at concentrations of (0, 40, and 60 g.l-1). Vitamin C(vit C), enzyme activity, Ascorbate peroxidase (Apx), and Amylase  enzymes, Proline amino acid and β- carotene were quantified by high-performance Performance Liquid Chromatography (HPLC). Results revealed that, highest contents of (Apx) 128.16 µg. ml-1 and 132.6 µg. ml-1 for amylase at 60 g.l-1 of mannitol and 0 Gy of gamma, respectively. Furthermore, the content of VIT C (265.57 µg. ml-1 ) at 20 Gy and 60 g.l-1 of mannitol. The results also showed that a combination of 40 Gy and 60 g.l-1 of mannitol was optimum for the production of high proline amino acids (761.0 µg. ml-1 )  and  (113.54 µg. ml-1 )  for β- carotene  content in callus culture.